Distributed ledger technologies in securities post-trading - Revolution or evolution? - Andrea Pinna; Wiebe Ruttenberg (European Central Bank (ECB), 2016)
Over the last decade, information technology has contributed significantly to the evolution of financial markets, without, however, revolutionising the way in which financial institutions interact with one another. This may be about to change, as some market players are now predicting that new database technologies, such as blockchain and other distributed ledger technologies (DLTs), could be the source of an imminent revolution. This paper analyses the main features of DLTs that could influence their potential adoption by financial institutions and discusses how the use of these technologies could affect the European post-trade market for securities. The original protocol underlying DLTs has its roots in the anarchic world of virtual currencies, which operate outside the conventional financial system. The public debate on DLTs has also been very much focused on the revolutionary potential of the technology. This paper concludes that, irrespective of the technology used and the market players involved, certain processes that feature in the post-trade market for securities will still need to be performed by institutions. DLTs could, however, stimulate a reorganisation of financial markets, which could in turn: (i) reduce reconciliation costs, (ii) streamline the post-trade value chain, and (iii) allow more efficient use to be made of collateral and regulatory capital. It should, nevertheless, be remembered that research into DLTs and their uses is at an early stage. The scope for financial institutions to adopt DLTs and their potential impact on mainstream financial markets are still unclear. This paper discusses three potential models of how market players could adopt DLTs for performing core post-trade functions. The DLT could be adopted either: (i) in clusters, (ii) collectively, or (iii) peer to peer. The evaluation of the three adoption models assumes that they are all equally compatible with the regulatory framework. It shows that, assuming this to be the case, they would each have different advantages and costs.
Keywords: G21; G23; L15; O33; 330; Bitcoin; blockchain; clearing; distributed ledger technologies; financial market infrastructures; fintech; settlement